Status of adrenals at influence exogenous RNA in the conditions of the experimental blastomogenesis. - Khripkov, I. S. (Морфологія / Morphologia / Morfologìâ, 2011)
The experimental research has been supplied on 70 white rats - males in mass of 140-160 to whom under a skin the tumoral strain of a carcinoma of Guerin has been transplanted. The operation purpose was learning of influence exogenous homologous tumoral RNA on a morfo-functional status of adrenals at animals with tumor. Tumour growth causes a strain of compensator mechanisms of adrenals at cellular level and is accompanied by response from a microcirculatory channel. Introduction exogenous homologous tumoral RNA an animal locks development of reactive changes in a parenchima and an organ stroma.